Long-Chain Acylcarnitines and Cardiac Excitation-Contraction Coupling: Links to Arrhythmias - Aitken-Buck, Hamish M.; Krause, Julia; Zeller, Tanja; Jones, Peter P.; Lamberts, Regis R. (Frontiers in Physiology, 2020)
A growing number of metabolomic studies have associated high circulating levels of the amphiphilic fatty acid metabolites, long-chain acylcarnitines (LCACs), with cardiovascular disease (CVD) risk. These studies show that plasma LCAC levels can be correlated with the stage and severity of CVD and with indices of cardiac hypertrophy and ventricular function. Complementing these recent clinical associations is an extensive body of basic research that stems mostly from the 20th century. These works, performed in cardiomyocyte and multicellular preparations from animal and cell models, highlight stereotypical derangements in cardiac electrophysiology induced by exogenous LCAC treatment that promote arrhythmic muscle behaviour. In many cases, this is coupled with acute inotropic modulation; however, whether LCACs increase or decrease contractility is inconclusive. Linked to the electromechanical alterations induced by LCAC exposure is an array of effects on cardiac excitation-contraction coupling mechanisms that overload the cardiomyocyte cytosol with Na+ and Ca2+ ions. The aim of this review is to revisit this age-old literature and collate it with recent findings to provide a pathophysiological context for the growing body of metabolomic association studies that link circulating LCACs with CVD.